Eco-poetic Inquiries to inspire Eco-literacy: Practices of Joyful Connection to Earth - Kulnieks, Andrejs (Language and Literacy / Langue et littératie, 2025)
In my research I explore how practices of eco-poetic inquiry can support learners in developing ecological literacy by deepening their relationships with the Earth. Using examples from courses I teach in language and literacies at the secondary level in a teacher education program in Saskatchewan, I examine how eco-poetic practices also foster joy in this learning. Engaging with eco-poetic inquiries that ask students to describe the connections they have with local environments is a way of asking them to re-examine the relationships they have with the more than human world that can lead to a restoration of healthy relationships with local places.